Doxorubicin induces caspase-mediated proteolysis of KV7.1 - Strigli, Anne; Raab, Christian; Heßler, Sabine; Huth, Tobias; Schuldt, Adam J.T.; Alzheimer, Christian; Friedrich, Thomas; Burridge, Paul W.; Luedde, Mark; Schwake, Michael (Communications Biology, 2018)
Kv7.1 (KCNQ1) coassembles with KCNE1 to generate the cardiac IKs-channel. Gain- and loss-of-function mutations in KCNQ1 are associated with cardiac arrhthymias, highlighting the importance of modulating IKs activity for cardiac function. Here, we report proteolysis of Kv7.1 as an irreversible posttranslational modification. The identification of two C-terminal fragments of Kv7.1 led us to identify an aspartate critical for the generation of one of the fragments and caspases as responsible for mediating proteolysis. Activating caspases reduces Kv7.1/KCNE1 currents, which is abrogated in cells expressing caspase-resistant channels. Enhanced cleavage of Kv7.1 can be detected for the LQT mutation G460S, which is located adjacent to the cleavage site, whereas a calmodulin-binding-deficient mutation impairs cleavage. Application of apoptotic stimuli or doxorubicin-induced cardiotoxicity provokes caspase-mediated cleavage of endogenous IKs in human cardiomyocytes. In summary, caspases are novel regulatory components of IKs channels that may have important implications for the molecular mechanism of doxorubicin-induced cardiotoxicity.
EVALuna2:35830